1983
DOI: 10.1007/bf03007711
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of midazolam and thiopentone for induction of anaesthesia in Ill surgical patients

Abstract: The cardiovascular effects of mldazolam (0.15 mg kg -t ) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although midazolam is to be considered among the benzodiazepines, which further reduce blood pressure [12,20], this was not observed in the KET group. However, pressure reduction occurred with the use of isoflurane, confirming literature reports [6,16], and with findings by Vasconcellos et al [26] in Cebus apella.…”
Section: Discussionmentioning
confidence: 92%
“…Although midazolam is to be considered among the benzodiazepines, which further reduce blood pressure [12,20], this was not observed in the KET group. However, pressure reduction occurred with the use of isoflurane, confirming literature reports [6,16], and with findings by Vasconcellos et al [26] in Cebus apella.…”
Section: Discussionmentioning
confidence: 92%
“…Both midazolam and diazepam transiently depress the baroreflex function and decrease the sympathetic tone (Marty et al, 1986a). The reduction in MAP after midazolam induction in both healthy (Marty et al, 1986a;Lebowitz et al,1982) and ill patients (Marty et al, 1986b;Lebowitz et al, 1983) is reported to be 15-19% when measuring the blood pressure invasively, despite doses ranging from 0.15 to 0.30 mg kg'-1. This supports our findings of a maximal effect on blood pressure evoked by midazolam at lower, sedative doses with a maximum decrease on MAP of 18%.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, a variety of fluid regimes have been used around induction of general anaesthesia to ameliorate these combined effects of pre-operative fluid deficit, vasodilation and the cardiovascular depressant actions of anaesthetic drugs [12,13]. This study was designed to investigate the effect of a pre-operative infusion of crystalloid solution (to allow for the patients' maintenance requirements overnight, calculated as 1.5 ml.kg )1 .h )1 ) on pre-operative haemodynamic data, global oxygenation parameters and splanchnic perfusion.…”
mentioning
confidence: 99%